Effect of asset structure, liquidity on financial performance with leverage as a mediation (intervening) on companies listed Jakarta Islamic Index - Hanifa Yosmawardani -; Halkadri Fitra (Financial Management Studies, 2021)
This study aims to see the effect of asset structure, liquidity on financial performance with leverage as an intervening variable in companies listed on the Jakarta Islamic Index. This research is classified as a quantitative research. The population in this study were all companies listed in the Jakarta Islamic Index 2014-2019. The sample in this study was determined by purposive sampling, the criteria used to select the sample were all sharia-based companies listed on the Jakarta Islamic Index (JII) on the Indonesia Stock Exchange for the period 2014-2019; consecutive companies included in the Jakarta Islamic Index during 2014-2019. The sample in this study is 89 annual reports listed in the Jakarta Islamic Index which are included in the sample of this study. The type of data used is secondary data from the website www.idx.co.id. This study uses a data analysis approach, namely Structure Equation Modeling (SEM). The type of SEM method used in this research is Partial Least Square Path Modeling (PLS-SEM). The results of this study found that there is a direct and significant influence between asset structure and liquidity on leverage on the Jakarta Islamic Index; There is a direct and significant influence between asset structure, leverage on financial performance on the Jakarta Islamic Index; There is no significant direct effect between liquidity on financial performance on the Jakarta Islamic Index; There is an indirect and significant influence between asset structure and liquidity on financial performance through leverage as the mediating variable.